The voice from China : an CHEN on international economic law - CHEN, An (Understanding China,, 2013)
In short, the 24 selected and representative articles written in English by the author over the past 30-odd years, mainly published in international leading journals and now collected and compiled in this monograph, could be deemed the products of international academic debates. They record, reflect and embody the author's personal views on a number of contemporary basic issues in international economic law & the international economic order. These personal views with Chinese characteristics are deeply rooted in China's specific national situation and the common position of the world-wide weak groups, and are significantly and substantially different and independent from some existing voices from strong western powers, which is why the book bears the title "The Voice from China".